2015
DOI: 10.1007/s40614-015-0048-z
|View full text |Cite
|
Sign up to set email alerts
|

On Terms: Frequency and Rate in Applied Behavior Analysis

Abstract: The term Bfrequency^in applied behavior analysis and behavior measurement generally refers to cycles per unit time, or a count (usually of behavior) divided by the time during which it occurred. In statistics, however, the term refers to a count of items in a data set. This meaning of Bfrequency^as synonymous with Bcount^has been adopted by one major text and the Behavior Analyst Certification Board®. Another major text uses Bfrequency^and Brate^interchangeably when referring to behaviors per unit time. Both t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…This measure assesses frequency of outbursts due to anger (e.g., shouting, cursing, and throwing or breaking things when upset) during the past 7 days. A single rating is recorded for the total number of outbursts ( Merbitz et al, 2016 ).…”
Section: Assessmentmentioning
confidence: 99%
“…This measure assesses frequency of outbursts due to anger (e.g., shouting, cursing, and throwing or breaking things when upset) during the past 7 days. A single rating is recorded for the total number of outbursts ( Merbitz et al, 2016 ).…”
Section: Assessmentmentioning
confidence: 99%
“…Merbitz, Merbitz, and Pennypacker () recently identified a terminological problem in behavior analysis. The term frequency has been used as a reference to both the rate of a response (the number of responses per time) as well as its count (the number of responses).…”
Section: Use Of the Term Frequency In Behavior‐analytic Textbooksmentioning
confidence: 99%
“…We note that the JEAB and EABtextbook data indicate that frequency is generally not used in EAB, which places this particular terminological issue within the ABA domain. Merbitz et al (2016) identified that the examination task lists of the now-defunct Florida Behavior Analysis Certification Program (Starin, Hemingway, & Hartsfield, 1993) used frequency as rate, but that the Behavior Analyst Certification Board ® 's (BACB ® ) task lists have used frequency as count. The authors imply that recent examples of frequency as count in the literature are an influence of the BACB's activity.…”
mentioning
confidence: 99%